The urban-rural income gap and inequality in China - Terry Sicular; Ximing Yue; Björn Gustafsson; Shi Li (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Using new household survey data for 1995 and 2002, we investigate the size of China's urban-rural income gap, the gap's contribution to overall inequality in China, and the factors underlying the gap. Our analysis improves on past estimates by using a fuller measure of income, adjusting for spatial price differences and including migrants. Our methods include inequality decomposition by population subgroup and the Oaxaca- Blinder decomposition. Several key findings emerge. First, the adjustments substantially reduce China's urban-rural income gap and its contribution to inequality. Nevertheless, the gap remains large and has increased somewhat over time. Second, after controlling for household characteristics, location of residence remains the most important factor underlying the urban-rural income gap. The only household characteristic that contributes substantially to the gap is education. Differences in the endowments of, and returns to, other household characteristics such as family size and composition, landholdings, and communist party membership are relatively unimportant. – China ; urban-rural inequality ; income
Keywords: D31; O18; P25; 330; Regionale Einkommensverteilung; Stadt-Land-Beziehung; China